Role of Gefitinib in Patients With Recurrent or Metastatic Cervical Carcinoma Ineligible or Refractory to Systemic Chemotherapy: First Study From Asia. Issue 4 (1st May 2013) - Sharma, Daya Nand; Rath, Goura Kisor; Julka, Pramod Kumar; Gandhi, Ajeet Kumar; Jagadesan, Pandjatcharam; Kumar, Sunesh
Abstract : Objectives: There are limited options for patients with recurrent or metastatic cervical carcinoma who are either refractory to or ineligible for systemic chemotherapy. We conducted a clinical study to evaluate the role of gefitinib, an epidermal growth factor receptor tyrosine kinase inhibitor, in such patients. Methods: Eligible patients were enrolled into the study and were treated with gefitinib at a dose of 250 mg/day orally until disease progression, development of intolerable adverse effects, or withdrawal of consent. The primary end point of the study was progression-free survival. The secondary end points were stable disease, overall survival, and toxicity. Results: From January 2008 to June 2011, a total of 20 patients were enrolled. Median age was 52 years and median disease-free interval was 15 months. Twelve patients presented with locoregional recurrence, 2 patients presented with distant metastases, and 6 patients presented with both locoregional recurrence and distant metastasis. Median duration of gefitinib therapy was 4 months. One patient had complete response, 1 patient had partial response, 4 patients had stable disease, and 14 patients had progressive disease. The median progression-free survival and overall survival were 4 months and 5 months, respectively. Only 1 patient had severe drug-related toxicity. Conclusions: Gefitinib is safe and seems to be effective in recurrent or metastatic cervical carcinoma. Further studies are warranted to identify the subgroup of patients, based on epidermal growth factor receptor mutations, who are more likely to benefit.